Neutrophil-to-lymphocyte ratio is associated with increased cerebral blood flow velocity in acute bacterial meningitis - Giede-Jeppe, Antje; Atay, Selim; Koehn, Julia; Mrochen, Anne; Lücking, Hannes; Hölter, Philip; Volbers, Bastian; Huttner, Hagen B.; Hueske, Lena; Bobinger, Tobias (Scientific Reports, 2021)
In community-acquired bacterial meningitis (CABM) intracranial vascular alterations are devastating complications which are triggered by neuroinflammation and result in worse clinical outcome. The Neutrophil-to-Lymphocyte ratio (NLR) represents a reliable parameter of the inflammatory response. In this study we analyzed the association between NLR and elevated cerebral blood flow velocity (CBFv) in CABM-patients. This study included all (CABM)-patients admitted to a German tertiary center between 2006 and 2016. Patients’ demographics, in-hospital measures, neuroradiological data and clinical outcome were retrieved from institutional databases. CBFv was assessed by transcranial doppler (TCD). Patients’, radiological and laboratory characteristics were compared between patients with/without elevated CBFv. Multivariate-analysis investigated parameters independently associated with elevated CBFv. Receiver operating characteristic(ROC-)curve analysis was undertaken to identify the best cut-off for NLR to discriminate between increased CBFv. 108 patients with CABM were identified. 27.8% (30/108) showed elevated CBFv. Patients with elevated CBFv and normal CBFv, respectively had a worse clinical status on admission (Glasgow Coma Scale: 12 [9–14] vs. 14 [11–15]; p = 0.005) and required more often intensive care (30/30 [100.0%] vs. 63/78 [80.8%]; p = 0.01).The causative pathogen was S. pneumoniae in 70%. Patients with elevated CBFv developed more often cerebrovascular complications with delayed cerebral ischemia (DCI) within hospital stay (p = 0.031). A significantly higher admission-NLR was observed in patients with elevated CBFv (median [IQR]: elevated CBFv:24.0 [20.4–30.2] vs. normal CBFv:13.5 [8.4–19.5]; p < 0.001). Multivariate analysis, revealed NLR to be significantly associated with increased CBFv (Odds ratio [95%CI] 1.042 [1.003–1.084]; p = 0.036). ROC-analysis identified a NLR of 20.9 as best cut-off value to discriminate between elevated CBFv (AUC = 0.713, p < 0.0001, Youden's Index = 0.441;elevated CBFv: NLR ≥ 20.9 19/30[63.5%] vs. normal CBFv: NLR > 20.9 15/78[19.2%]; p < 0.001). Intracranial vascular complications are common among CABM-patients and are a risk factor for unfavorable outcome at discharge. Elevated NLR is independently associated with high CBFv and may be useful in predicting patients’ prognosis.
CRIS-Team Scopus Importer:2021-06-18